Heterogeneous cobalt catalysts for reductive amination with H2: general synthesis of secondary and tertiary amines. Issue 96 (3rd October 2016) - Mao, Fei; Sui, Dejun; Qi, Zhengliang; Fan, Haipeng; Chen, Rizhi; Huang, Jun
Abstract : Heterogeneous Co@NC catalysts were prepared, characterized and applied for the general synthesis of secondary and tertiary amines by Co-catalyzed reductive amination with H2 gas. Abstract : Heterogeneous Co@NC catalysts were prepared, characterized and applied for the reductive amination of aldehydes and ketones with H2 gas. The Co catalyst Co@NC (800-2 h) was found to be active and selective for the reductive amination of aldehydes and ketones using H2 gas. Thus, general synthesis of secondary and tertiary amines was developed by the Co-catalyzed reductive amination with H2 gas, and various secondary and tertiary amines can be obtained in high yields. Moreover, a practical synthesis of N -substituted isoindolinones was also presented by a one step process with the Co@NC (800-2 h) catalyst. The Co@NC (800-2 h) catalyst is reusable at least five times without evident loss of activity.